MANAJEMEN PEMBELAJARAN SENI BACA ALQURAN DI PONDOK PESANTREN ALQURAN AL-ITQON BOGOR - Muhammad Abdurrahman Efendi; Muhamad Entang; Rais Hidayat; Dian Wulandari (Universitas Pakuan, 2020)
LEARNING MANAGEMENT READ AL QURAN IN ALQURAN AL-ITQON BOARDING SCHOOL, BOGORThe art of reading Alquran at boarding school is the major program that could be a uniqueness for the institution and the strengths as well. The excellent output of reading Alquran will support the achievement of the school target, therefore the school needs to develop effective learning management, especially in reading Alquran. This research is focused on learning management in the art of reading Alquran at Al-Itqon Islamic Boarding School Bogor. The study was using a descriptive qualitative analytical approach to describe, explain and analyze objectively about the learning management of reading Alquran at Al-Itqon Boarding School Bogor. The data was taken by interviews about the sub-focus of the research, which were: planning, organizing, implementing and evaluating. The results showed that the learning management of the art of reading Alquran at the Al-Itqon Islamic Boarding School in Bogor, begin with planning as the first step, that consist of:1) setting the goal of the program which is preparing student to be a Qori or Qoriah, 2) setting the main program, which are tahsin and recital. The second step is organizing which consists of 1) setting the organizational structure for both male and female students, 2) organizing the program schedule, 3) organizing the facilitation such, learning method and media. The third step is an implementation: 1) learning steps implementation, 2) allocation of learning schedule and duration, 3) media and learning method. The final step is evaluation, which is setting the evaluation objectives including improving reading quality, remedial, repetition by drilling and awarding graduate certificates